Electrochemical Behaviour of Tinidazole at 1,4-Benzoquinone Modified Carbon Paste Electrode and Its Direct Determination in Pharmaceutical Tablets and Urine by Differential Pulse Voltammetry - Yosef Nikodimos; Beyene Hagos (Journal of Analytical Methods in Chemistry)
A simple and highly sensitive electrochemical method based on a 1,4-benzoquinone modified carbon paste electrode (1,4-BQMCPE) was described for the determination of tinidazole (TDZ). In Britton Robinson buffer solution, TDZ yields well-defined irreversible reduction peak at −0.344 V on a 1,4-BQMCPE. Compared with that on a bare CPE, the reduction peak of TDZ increased significantly on the modified CPE and the effects of different parameters on the voltammetric responses were also investigated. Differential pulse voltammetric method was proposed and optimized for TDZ determination and its reductive peak current response at 1,4-BQMCPE was found to show linear dependence on the concentration of TDZ in the range of 1.0 × 10−6 to 5.0 × 10−4 M with a linear regression equation, correlation coefficient, limit of detection (LOD), and limit of quantification (LOQ) of IPC (μA) = 0.19958 + 0.02657C (μM), 0.99486, 1.10 × 10−7 M, and 3.77 × 10−7, respectively. Excellent recovery results for spiked TDZ in pharmaceutical tablet samples ranging within 97.44–97.51% and in urine ranging within 95.37–96.91% were observed. The selectivity of the method for TDZ was further studied in the presence of selected potential interferents and confirmed the potential applicability of the developed method for the determination of TDZ.